The Difference in Abnormal Return and Trading Volume Activity Analysis During and After Presidential Election on 17 April 2019 In Transport, Infrastructure and Utility Company Listed in Indonesia Stock Exchange In 2019 - Nafasati, Febrina; Indudewi, Dian; Mansur, Abu (Universitas Semarang, 2021)
This study is an event study that aims to analyze whether or not there are any differences in Abnormal Returns Stock and Trading Volume Activity before and after the Presidential Elections on April 17, 2019 in the Indonesian Stock Exchange (IDX). 45 companies were observed for five-day before and after five days the event become samples of this study. In this study the independent variable is the election of the President and Vice President, while the dependent variable is Abnormal Return Stock and Trading Volume Activity. This study uses an event study, where observations are made on the average abnormal return of stocks and trading volume activity for five days before and after the event. The test equipment in this study used the Wilcoxon Sign Rank Test. The results of this study indicate that there are significant differences in abnormal returns stock and trading volume activity before and after the election of the President and Vice President on April 17, 2019.